Discrete Implementation of a PI Controller for Three-Phase PWM Rectifier - Nurwati, Tri; Gradianto, Gasa; Siswoyo, Bambang; Bashir Mosaddegh; I Nyoman Wahyu Satiawan (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2024)
Rectifiers are becoming more prevalent in a wide range of applications, including power supplies for microelectronics, household electrical devices, battery charging, and power conversion in high-voltage direct current (HVDC) transmission systems. Conventional rectifiers often employ uncontrolled diodes, which have the drawback of generating a fixed output voltage that cannot be modified. There is a requirement for a regulated rectifier, specifically a three-phase PWM Rectifier that transforms AC voltage into DC voltage with an output voltage that surpasses the input voltage and can be modified as per requirements. This study explores the comparison between s-domain and z-domain PI controller designs in the context of controlling a three-phase pulse width modulation (PWM) rectifier. Applying the dual-closed-loop control technique with the pole-zero cancellation approach, we can calculate the PI parameters for controlling the current and voltage in the circuit. The values of the parameters are as follows: K_pc = 4, K_ic = 100, K_pv = 0.097, and K_iv = 4.85. Applying the forward Euler method to transform the PI controller from the s domain to the z domain. The test results for the PWM Rectifier PI controller were conducted in both the s-domain and z-domain. As per the setpoint, a three-phase voltage source with a value of 220 Volts was used, resulting in a stable DC voltage output of 600 Volts.